Energy consumption vs. users' perceptions: A quantitative study of energy and comfort in university campus - Syed Yahya, S.N.N.; Mohd Ariffin, A.R.; Ismail, M.A. (2015)
The relationship between users' perceptions of comfort and energy performance is an important integration of society with the environment which also have indirect implications to the economy. Achieving users' comfort in buildings involves the use of energy where multiple studies have associated energy use via heating and cooling as predictors of users' comfort. However, these studies have neglected the magnitude of energy needed to achieve comfort. Therefore, the current paper investigates the quantum of electricity used in a public university to achieve users' comfort. The investigation adopts the quantitative method of comparing electricity consumption and users' comfort via two different instruments namely; energy loggers and occupant survey. An energy logger was installed on three study buildings while an occupant survey was distributed to users of the same buildings. Benchmarking was used to compare energy indices of the study buildings. It was found that the study building with the highest energy index also scored the highest perception of comfort by the users. As thermal control for indoor comfort account for more than half of the total electricity consumption, the result suggested that electricity consumption predicts users' comfort positively.However, the ratio of energy consumed and comfort achieved is questionable. This study suggests that a substantial amount of electricity is needed to achieve a small measure of comfort. Additionally, the study also revealed that two of the study buildings performed poorly in terms of energy performance while one performed fairly well with the potential of becoming an energy-efficient building. By replicating the study to other buildings, the research can help identify energy-efficient potentials in buildings towards reducing the campus' energy consumption holistically.